2021
DOI: 10.1007/s00520-021-06235-4
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb sensory evaluations and ultrasonographic skin measurements in breast cancer–related lymphedema receiving complex decongestive physiotherapy

Abstract: Purpose The aims of this study were to investigate if/how the presence of lymphedema affects the sensation of the upper limb and to assess whether complex decongestive physiotherapy (CDP) has a favorable impact on sensory testing. Methods A total of 27 patients with unilateral stage 2 breast cancer–related lymphedema (BCRL) were included in the study. Bilateral circumferential measurements were taken with a tape measure at different levels. Based on these measurements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(40 reference statements)
2
2
0
Order By: Relevance
“…However, a trend towards higher thresholds (i.e., poorer acuity) in women with objective and subjective BCRL compared to the control group was noted. To our knowledge, perceptual acuity using the two-point discrimination test has only been previously explored in a small sample of women with BCRL [42]. This study showed similar results with a decreased sensory perception at the affected side compared to the non-affected side [42].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, a trend towards higher thresholds (i.e., poorer acuity) in women with objective and subjective BCRL compared to the control group was noted. To our knowledge, perceptual acuity using the two-point discrimination test has only been previously explored in a small sample of women with BCRL [42]. This study showed similar results with a decreased sensory perception at the affected side compared to the non-affected side [42].…”
Section: Discussionsupporting
confidence: 70%
“…To our knowledge, perceptual acuity using the two-point discrimination test has only been previously explored in a small sample of women with BCRL [42]. This study showed similar results with a decreased sensory perception at the affected side compared to the non-affected side [42]. A negative body image, including these altered perceptions, after breast cancer have been described extensively [20,43].…”
Section: Discussionsupporting
confidence: 70%
“…Measuring pain during other phases may be associated with differentiation between BCRL and other causes of pain [ 28 ], considering BCRL tends to be described as achy and heavy, but not necessarily ‘painful’[ 29 ]. It is evident that BCS with BCRL experience sensory changes, including reduced light touch, static and moving two-point discrimination, pressure pain threshold, and tactile localization sensations, which can improve with complete decongestive therapy [ 30 ]. For consistency, the study management and advisory groups advise to consider measuring pain and sensation for all phases.…”
Section: Discussionmentioning
confidence: 99%
“…CDT comprises four integral steps, encompassing skin care, freehand lymphatic drainage, compression bandaging, and functional exercise ( 39 41 ). A multitude of scholarly investigations has been dedicated to the study of CDT, evaluating its efficacy through various means.Some studies have focused on assessing the effectiveness of CDT using ultrasound ( 42 , 43 ) or BIS ( 44 ) to gauge its impact on edema reduction. Additionally, comprehensive evaluations of CDT’s effects on pain, quality of life, mood, and fatigue in BCRL patients have been conducted ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%